Market resource gaps: Identifying resources to cocreate solutions that facilitate consumption. (September 2017) - Abendroth, Lisa J.; Pels, Jaqueline
The needs of low-income consumers in emerging markets often go unfulfilled. In this article, we integrate literature related to cocreation, market separation, and the 4As (acceptability, affordability, accessibility, and awareness) into a new conceptual framework on market resource gaps. The framework allows firms to determine the nature and extent of the gaps between themselves and consumers that limit consumption while simultaneously identifying resources for potential integration into new solutions that can resolve these gaps. The framework also recognizes market dynamics and can be employed iteratively to enable continuous innovation.